Outcomes of a young ARV clinic within an established Family Practice - Zandy Rosochacki; Mark C. Hosking (South African Family Practice)
The letter reports on outcomes of a private HIV/AIDS clinic and questions its safety. The clinic (site 282) is a satellite to a PEPFAR (presidents emergency program for aids relief) funded and AURUM health supervised program. The clinic identifies itself from being different to the other programs in that it operates from within an established private Family Practice, has two specific doctors and limited counseling and no nurse support. In the rest of its content it has the same constraints as the government clinics. Using four recently published reports on HIV/AIDS programs it compares and comments on early outcome data. The conclusion is that provided good data are kept and improved with time, it would be safe to continue in this model.